AhR Mediated Activation of Pro-Inflammatory Response of RAW 264.7 Cells Modulate the Epithelial-Mesenchymal Transition - Padhmavathi Selvam; Chih-Mei Cheng; Hans-Uwe Dahms; Vinoth Kumar Ponnusamy; Yu-Yo Sun (Toxics, 2022)
Pulmonary fibrosis, a chronic lung disease caused by progressive deterioration of lung tissue, is generated by several factors including genetic and environmental ones. In response to long-term exposure to environmental stimuli, aberrant tissue repair and epithelial cell-to- mesenchymal cell transition (EMT) trigger the subsequent progression of pulmonary fibrotic diseases. The Aryl hydrocarbon receptor (AhR) is a transcription factor that is activated by ligands providing lung dysfunction when activated by environmental toxins, such as polycyclic aromatic hydrocarbons. Our previous study demonstrated that AhR mediates α-SMA expression by directly binding to the α-SMA (fibroblast differentiation marker) promoter, suggesting the role of AhR in mediating fibrogenic progression. Here we follow the hypothesis that macrophage infiltrated microenvironments may trigger inflammation and subsequent fibrosis. We studied the expression of cytokines in RAW 264.7 cells by AhR activation through an ELISA assay. To investigate molecular events, migration, western blotting and zymography assays were carried out. We found that AhR agonists such as TCDD, IP and FICZ, promote the migration and induce inflammatory mediators such as TNF-α and G-CSF, MIP-1α, MIP-1β and MIP-2. These cytokines arbitrate EMT marker expression such as E-cadherin, fibronectin, and vimentin in pulmonary epithelial cells. Expression of proteins of MMPs in mouse macrophages was determined by zymography, showing the caseinolytic activity of MMP-1 and the gelatinolytic action of MMP-2 and MMP-9. Taken together, the present study showed that AhR activated macrophages create an inflammatory microenvironment which favours the fibrotic progression of pulmonary epithelial cells. Such production of inflammatory factors was accomplished by affecting the Wnt/β-catenin signalling pathway, thereby creating a microenvironment which enhances the epithelial-mesenchymal transition, leading to fibrosis of the lung.